Students’ Problem Solving Skills of Physics on the Gas Kinetic Theory Material - Wartono Wartono; Agus Suyudi; John Rafafy Batlolona (Journal of Education and Learning (EduLearn), 2018)
Some research aiming to improve problem-solving skills in physics by various learning models has been performed. So far, there is no comprehensive research that uses Inquiry-discovery learning model to improve problem solving skills (PSS) in physics with the aid of the PhET simulation in the material of kinetic theory of gases. This research aims to investigate the differences of PhET-aided Inquiry-discovery learning using a theoretical review on PSS in the material of kinetic theory of gases between the experimental class and control class. This research is a quasi-experimental study by a post-test only design. The data analysis was performed via a t-test. The analysis results showed students in the experimental get higher PSS class than those in the control class. Also, the students in the experimental class have the highest and lowest initial abilities which were still higher than the students in the control class. Hence, the inquiry-discovery learning model is recommended to enhance students’ physics PSS. The implication of this research is to provide information that students can be empowered by inquairy-discovey learning model in improving PSS. Therefore, it is expected that the next researchers can explore students’ PSS at each meeting in order to improve students’ learning outcomes.